Managing business risk a practical guide to protecting your business - Reuvid, Jonathan; Gale Group (London Kogan Page, 2005)
This second edition of a practical guide to potential areas of risk within a business is filled with expert advice from existing and new contributors including leading consultants, lawyers, regulatory authorities and risk management specialists. Managing Business Risks brings you up to date with the latest thinking and techniques for managing risk in a structured and integrated way.
Part 1: Strategic transformation -- Part 2: Change and continuity -- Part 3: Governance and control -- Part 4: Integrity and accountability -- Part 5: Legal considerations -- Part 6: Financial risks -- Part 7: Knowledge and systems -- Part 8: At work -- Part 9: Catastrophe and loss.
196 p. from about this publication (viewed August 26, 2008)
Electronic reproduction.
Keywords: Risk management; Electronic books